The Enigma of India's Arrival: A Review of Arvind Virmani's Propelling India: From Socialist Stagnation to Global Power - Basu, Kaushik (Journal of Economic Literature, 2008)
India's high growth over the last fifteen years has inspired several recent books and papers to examine the growth's source and sustainability—the two-volume study by Arvind Virmani being a case in point. This paper evaluates these recent works. It is argued that the cause of the take-off does not fit into any easy ideological category as suggested by Virmani. The current high growth has been achieved in several steps, with distinct factors of propulsion behind each step. There is reason to expect the growth to be sustainable, although destabilizing political tensions will arise from the increasing inequality. The paper also evaluates how India's growth relates to the global economy.